MEDIA FLASH CARD UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI EKSPRESIF PADA ANAK DENGAN AUTISME DI PENDIDIKAN ANAK USIA DINI - Depa Nursita; Lukman Hamid; Nisa Nurhidayah (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2020)
Children with autism have differences in communication, interaction and behavior skills compared to other children. Because children with autism cope with existing difficulties, children have difficulty expressing whatever is happening in others.Communication aspects that must be trained in children with autism in addition to speaking, namely gestures with the help of media such as pictures (visual). This study aims to study the expressive communication skills of autistic children using flash card media in early childhood education institutions. This study uses qualitative descriptive methods. The technique used is observation and interview. The results of the study prove that the use of flash card media can help to develop the communication skills provided to children with autism. So it can be concluded from this study that the use of flash card media can be used to train the communication skills of children with autism and can be used as a reference learning method for parents, teachers, institutions and prospective teachers.